TREATING THE USED AUTOMOBILES OILS USING SOLVENTS - A. R. Rassoul, Ghiyath; S. Mahmmoud, Laith (Iraqi Journal of Chemical and Petroleum Engineering, 2010)
Used automobile oils were subjected to filtration to remove solid material and dehydration to remove water, gasoline and light components by using vacuum distillation under moderate pressure, and then the dehydrated waste oil is subjected to extraction by using liquid solvents. Two solvents, namely n-butanol and n-hexane were used to extract base oil from automobile used oil, so that the expensive base oil can be reused again.The recovered base oil by using n-butanol solvent gives (88.67%) reduction in carbon residue, (75.93%) reduction in ash content, (93.73%) oil recovery, (95%) solvent recovery and (100.62) viscosity index, at (5:1) solvent to used oil ratio and (40 oC) extraction temperature, while using n-hexane solvent gives (60.25%) reduction in carbon residue, (76.54%) reduction in ash content, (89.06%) oil recovery, (94.78%) solvent recovery and (100.3) viscosity index, at (6:1) solvent to used oil ratio and (50 oC) extraction temperature.